Pengaruh Minat Belajar Siswa Terhadap Hasil Belajar Mata Pelajaran IPS Geografi di SMA Negeri 13 Buru Selatan Kecamatan Kepala Madan Kabupaten Buru Selatan - Nurfitri, Wa Ode; Salakory, Melianus; Manakane, Susan Evelin (GEOFORUM, 2025)
This study was motivated by the low student engagement in Geography learning at SMA Negeri 13 Buru Selatan, Kecamatan Kepala Madan. The aim was to determine the extent to which learning interest influences students’ academic achievement. The research employed a quantitative approach with an ex post facto method. The sample consisted of 30 students from grades X and XI, selected through purposive sampling. Research instruments included questionnaires on learning interest and learning outcomes, analyzed using simple regression, Pearson correlation, t-test, and ANOVA. Findings revealed that learning interest was categorized as moderate to high with an average score of 47.7 out of 55. Students’ learning outcomes were also considered good with an average score of 39.37 out of 45. Regression analysis yielded the equation Y = 23.722 + 0.338X with a significance value of 0.046 (<0.05), indicating a significant influence of learning interest on achievement. These results highlight the importance of interactive and contextual teaching strategies that enhance participation, attention, and curiosity. The implication is that teachers should implement engaging methods, schools need to provide supportive learning environments, and students are encouraged to strengthen their intrinsic motivation to achieve optimal outcomes